Process intervention to assure sanitation of beef carcasses and cuts - Prasai, R.K.; Kenney, P.B.; García Zepeda, C.M.; Mease, L.E.; Vogt, L.R.; Willard, B.L.; Kropf, Donald H.; Phebus, Randall K.; Campbell, R.E.; Boyle, Elizabeth A. E.; Kastner, Curtis L.; Fung, Daniel Y. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The meat industry and Food Safety and Inspection Service (FSIS) strive to minimize carcass contamination during slaughter and subsequent processing. Because microbial contamination during slaughter cannot be avoided completely, decontamination methods must be addressed. This overview emphasizes process intervention studies conducted at Kansas State University to determine the most effective intervention points and technologies to control microbiological hazards in meat and meat products. Our research shows that trimming of gross contamination followed by washing is a reasonable approach to minimizing microbial contamination on beef carcasses. We also found that sanitation of subprimal cuts may be just as effective as treating the carcass.
Keywords: Beef; Sanitation; Carcass; Cuts